2020
DOI: 10.1111/jace.17008
|View full text |Cite
|
Sign up to set email alerts
|

Atomistic understanding of surface wear process of sodium silicate glass in dry versus humid environments

Abstract: Understanding surface reactions of silicate glass under interfacial shear is critical as it can provide physical insights needed for rational design of more durable glasses. Here, we performed reactive molecular dynamics (MD) simulations with ReaxFF potentials to study the mechanochemical wear of sodium silicate glass rubbed with amorphous silica in the absence and presence of interfacial water molecules. The effect of water molecules on the shear‐induced chemical reaction at the sliding interface was investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 46 publications
1
33
1
Order By: Relevance
“…The suppression of wear by water lubricants was also observed in ReaxFF simulations of sodium silicate sliding on amorphous silica [80,81]. Specifically, water was found to inhibit mechanochemical wear by suppressing the formation of Si silica -O-Si silicate bonds, consistent with experimental trends showing that wear decreased with increasing humidity [80]. Further, experiments revealed subsurface densification of glass during sliding, which was then explained by the simulations as shear-driven change of the subsurface Si-O-Si bond angle and Si-O bond length distributions [81].…”
Section: Reactions Between Lubricants and Surfacesmentioning
confidence: 59%
See 1 more Smart Citation
“…The suppression of wear by water lubricants was also observed in ReaxFF simulations of sodium silicate sliding on amorphous silica [80,81]. Specifically, water was found to inhibit mechanochemical wear by suppressing the formation of Si silica -O-Si silicate bonds, consistent with experimental trends showing that wear decreased with increasing humidity [80]. Further, experiments revealed subsurface densification of glass during sliding, which was then explained by the simulations as shear-driven change of the subsurface Si-O-Si bond angle and Si-O bond length distributions [81].…”
Section: Reactions Between Lubricants and Surfacesmentioning
confidence: 59%
“…Subsequent simulations were performed at a range of temperatures and with varying amounts of water and revealed that both factors affected the formation of covalent bonds that bridge the two solid surfaces [77]. The suppression of wear by water lubricants was also observed in ReaxFF simulations of sodium silicate sliding on amorphous silica [80,81]. Specifically, water was found to inhibit mechanochemical wear by suppressing the formation of Si silica -O-Si silicate bonds, consistent with experimental trends showing that wear decreased with increasing humidity [80].…”
Section: Reactions Between Lubricants and Surfacesmentioning
confidence: 89%
“…Based on a general relationship between bond distance and bond order, 37 the ReaxFF‐MD provides us a comprehensive understanding of the formation and dissociation of interfacial bonds during the tribochemical wear process. It has been reported that the glass surface reactivity, 38 as well as the formation and breakage of interfacial Si particle –O–Si glass bridge bonds are the most fundamental mechanisms for the material removal process in the mechanically induced chemical bond removal mode 39,40 …”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that the glass surface reactivity, 38 as well as the formation and breakage of interfacial Si particle -O-Si glass bridge bonds are the most fundamental mechanisms for the material removal process in the mechanically induced chemical bond removal mode. 39,40 On the other hand, it is worth reminding that there is a threshold force, f, for both BK7 glass and fused silica glass to undergo material removal (as shown in Figure 4). This phenomenon can be understood as follows.…”
Section: Materials Removal Mechanismsmentioning
confidence: 99%
“…Further studies suggested this unusual wear behavior of SLS glass in humid air could be attributed to the presence of leachable sodium ions (Na + ) and the water activity on the glass surface 21–24 . Since the glass wear in humid air involves chemical reactions of water molecules adsorbed on the glass surface, 25–27 it is usually called “mechanochemical” wear and should be differentiated from ‘mechanical’ wear (or abrasive scratch) occurring in dry condition. The wear behavior of SLS glass can be further affected by the sliding speed 28 and the counter‐surface chemistry 25,29 …”
Section: Introductionmentioning
confidence: 99%